The influence of GSTP1 A313G polymorphism on susceptibility, chemotherapy-related toxicity and prognosis of Hodgkin’s lymphoma in Ukrainian patients - Kriachok, I.A.; Khranovska, N.M.; Svergun, N.M.; Filonenko, K.S.; Novosad, O.I.; Titorenko, I.B.; Martynchik, A.V.; Gubareva, H.O.; Kadnikova, T.V.; Aleksik, O.M.; Kushchevyy, E.V.; Pastushenko, I.V. (Вiopolymers and Cell, 2012)
The aim of this research was to study the influence of GSTP1 A313G polymorphism on susceptibility, chemotherapy-related toxicity and prognosis of Hodgkin’s lymphoma in Ukrainian patients. Methods. The polymorphic variants of GSTP1 gene were analyzed using Allelic Discrimination Real-Time PCR. Results. The GSTP1 polymorphism is not directly involved in the development of Hodgkin’s lymphoma and chemotherapy-related toxicity, but homozygous wild genotype of this gene is associated with a worse clinical response to the therapy and a higher risk of relapse. Conclusions. The investigation of GSTP1 polymorphism is very promising, since it might provide a possible application of this genetic marker as an independent prognostic factor of Hodgkin’s lymphoma. Мета. Дослідити поліморфізм гена GSTP1 A313G і визначити його вплив на виникнення лімфоми Ходжкіна, токсичність хіміотерапії, а також на перебіг захворювання. Методи. Поліморфні варіанти гена GSTP1 аналізували методом алель-специфічної ПЛР з детекцією результатів у режимі реального часу. Результати. Встановлено, що гомозиготний тип успадкування алеля дикого типу – генотип A/A – пов’язаний з несприятливим прогнозом перебігу лімфоми Ходжкіна: гіршою відповіддю на терапію і вірогідністю появи рецидивів. Висновки. Перспективним напрямком пошуку чинників впливу на перебіг хвороби є вивчення поліморфізму гена GSTP1, який у майбутньому може бути використаний як «фактор ризику» при формуванні прогностичних груп хворих та виборі тактики лікування. Цель. Исследовать полиморфизм гена GSTP1 A313G и определить его влияние на возникновение лимфомы Ходжкина, токсичность химиотерапии, а также на течение заболевания. Методы. Полиморфные варианты гена GSTP1 анализировали методом аллель-специфической ПЦР с детекцией результатов в режиме реального времени. Результаты. Установлено, что гомозиготный тип наследования аллеля дикого типа – генотип A/A – ассоциирован с неблагоприятным прогнозом течения лимфомы Ходжкина: худшим ответом на лечение и вероятностью появления рецидивов. Выводы. Перспективным направлением поиска причин, обусловливающих течение болезни, является изучение полиморфизма гена GSTP1, который в будущем, возможно, будет использован как «фактор риcка» при формировании прогностических групп больных и выборе тактики лечения.